Effect of Antibiotics and Gut Microbiota on the Development of Sepsis in Children with Hematopoietic Stem Cell Transplants - Potes, Daniela; Benavides, Iván Darío; Rivera-Franco, Nelson; Portilla, Carlos A.; Ramirez, Oscar; Castillo, Andrés; López-Medina, Eduardo (Journal of Pediatric Infectious Diseases, 2023)
Objective To describe the association between antibiotic use, gut microbiota composition, and the development of sepsis in pediatric patients undergoing hematopoietic stem cell transplantation (HSCT) to treat acute lymphoblastic leukemia.Methods A cohort of pediatric patients was followed up between days −30 (pre-HSCT) and +30 (post-HSCT), and sequential stool samples were collected for analysis of the taxonomic composition of bacterial communities by comparing the sequences of the 16s ribosomal RNA gene. Clinically, patients were divided into those with or without sepsis according to their clinical and laboratory data. Gut microbiota was categorized as potentially pathogenic or commensal and was described according to antibiotic use in patients with and without sepsis.Results A cohort of eight patients provided 34 stool samples at different time points during their pre- and post-HSCT periods. There was a greater diversity in the microbial composition in patients who did not develop sepsis. In contrast, patients who developed sepsis had low microbiota diversity, a slight dominance of the genus Bacteroides and order Enterobacterales, and a low abundance of the genus Akkermansia. The use of antibiotics was associated with a low relative abundance of commensal bacteria, a high relative abundance of potentially pathogenic microbiota, and a risk of sepsis.Conclusion Our results suggest that gut microbiota sequencing in pediatric HSCT recipients could predict the clinical course and guide direct interventions to improve patient outcomes. Accordingly, short-spectrum, tailored antibiotic therapy could be provided to patients with fever pre- and post-HSCT to prevent dysbiosis and reduce the risk of sepsis.
Keywords: gastrointestinal microbiota; sepsis; acute lymphoblastic leukemia; children; hematopoietic stem cell transplantation; dysbiosis